2006
DOI: 10.2172/911819
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Reflection Project Near the Southern Terminations of the Lost River and Lemhi Faults, Eastern Snake River Plain, Idaho

Abstract: SUMMARYThirteen seismic reflection lines were processed and interpreted to determine the southern terminations of the Lost River and Lemhi faults along the northwest boundary of the eastern Snake River Plain (ESRP). The southernmost terminations of the Arco and Howe segments were determined to support characterization of the Lost River and Lemhi fault sources, respectively, for the INL probabilistic seismic hazard analysis.Four commercial seismic reflection lines (Arco lines 81-1 and 81-2; Howe lines 81-3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…The mountain ranges adjacent to these normal faults end abruptly at the physiographic boundary of the eastern Snake River Plain. At the ends of the ranges, bedrock structural features, gravity data, and seismic refl ection data suggest that significant seismogenic fault movements do not extend into the eastern Snake River Plain (Mabey, 1978;Bruhn et al, 1992;Jackson et al, 2006). Some investigators, however, suggest that the normal faults extend into the eastern Snake River Plain and may be covered over by Quaternary basalt fl ows (e.g., Rodgers et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The mountain ranges adjacent to these normal faults end abruptly at the physiographic boundary of the eastern Snake River Plain. At the ends of the ranges, bedrock structural features, gravity data, and seismic refl ection data suggest that significant seismogenic fault movements do not extend into the eastern Snake River Plain (Mabey, 1978;Bruhn et al, 1992;Jackson et al, 2006). Some investigators, however, suggest that the normal faults extend into the eastern Snake River Plain and may be covered over by Quaternary basalt fl ows (e.g., Rodgers et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent faulting is evidenced by the 1983 moment magnitude (M) 6.9 Borah Peak, Idaho, earthquake, which ruptured the central segment of the Lost River fault with oblique normal slip that included a 17% sinistral component (Crone et al, 1987). At the southern ends of the three normal faults and within the proposed Centennial shear zone, bedrock structural features inferred from gravity and seismic-refl ection data suggest that signifi cant fault offsets do not extend into the eastern Snake River Plain (Mabey, 1978;Jackson et al, 2006). However, short and generally left-stepping, en echelon, NWtrending normal faults and monoclinal fl exures expressed in 400-730 ka basalt fl ows within the eastern Snake River Plain may be interpreted as slip on the Lost River fault (Kuntz et al, 1994(Kuntz et al, , 2002.…”
Section: Geologic Settingmentioning
confidence: 99%
“…Alternatively, others interpret the short normal faults and monoclines to be tectonic in origin and related to slip on the Arco segment (Wu and Bruhn, 1994;Kuntz et al 2002). Jackson et al (2006) interpreted both west-and east-dipping faults on seismic reflection lines AR2 and AR3 in Figure 4-16 acquired in the Arco VRZ and suggested that the normal faults and monoclines could be products of dike intrusion. They also suggested that the westdipping faults on lines AR1 and AR2 may be associated with slip on the Arco segment to a distance of 4.6 km south of its mapped location at the end of the Lost River Range (Figure 4-16).…”
Section: Eastern Snake River Plainmentioning
confidence: 99%
“…The Lemhi fault may terminate just south of the Lemhi range (Figure 4-16). Seismic reflection line SC1 shows a southwest dipping fault, which is thought to be the southernmost extent of the Lemhi fault and two the south, lines SC2 and SC3 show flat lying continuous reflections (Jackson et al, 2006). Although limited investigations have been performed, interpretations of regional gravity data suggest the Birch Creek valley may partially extend into the ESRP and that a volcanic vent may be aligned with a splay fault of the Beaverhead fault (Figure 4-10) (Woodward-Clyde Federal Services et al, 1996).…”
Section: 49mentioning
confidence: 99%